Trends in collisions between vessels and North Pacific humpback whales (Megaptera novaeangliae) in Hawaiian waters (1975–2011) - Lammers, M. O.; Pack, A. A.; Lyman, E. G.; Espiritu, L. (J. Cetacean Res. Manage., 2023)
Injury from collisions with vessels is a growing threat worldwide for many species of whales. Thirty seven years of historical records were examined for evidence of vessel collisions with humpback whales in the main Hawaiian Islands. Between 1975 and 2011, 68 collisions between vessels and whales were reported including 59 witnessed collisions and 9 observed whale injuries that were consistent with a recent vessel collision. No collisions were immediately lethal. The waters between Maui, Molokai, Lanai and Kahoolawe, which are known to have one of the highest concentrations of humpback whales in the Hawaiian Islands, had the highest incidence of collisions. Over 63% of the collisions involved calves and subadults, suggesting a greater susceptability towards collisions among younger animals. The rate of collisions increased significantly over the final twelve breeding seasons of the study and was greater than predicted by the estimated annual increase in the whale population, suggesting that the rising number of reported collisions cannot be explained solely by the annual increase in whale abundance. Although the total number of registered vessels and shipping traffic in Hawaii remained relatively constant between 2000 and 2010, there was a significant increase in the number of vessels between 7.9m and 19.8m in length. Vessels within this size range were also the most commonly involved in collisions during the study period, accounting for approximately two thirds of recorded incidents. It is concluded that from 1975–2011, there was a significant increase in reports of non-lethal collisions between vessels and humpback whales, especially calves and subadults, in the main Hawaiian Islands that likely reflects a combination of factors including the recovery of the population of North Pacific humpback whales, increases in traffic of particular vessel types, and increased reporting practices by operators of vessels.